2019
DOI: 10.1177/1073191119858407
|View full text |Cite
|
Sign up to set email alerts
|

Circular Modelling of Circumplex Measurements for Interpersonal Behavior

Abstract: This article describes a new way to analyze data from the interpersonal circumplex (IPC) for interpersonal behavior. Instead of analyzing Agency and Communion separately or analyzing the IPC’s octants, we propose using a circular regression model that allows us to investigate effects on a blend of Agency and Communion. The proposed circular model is called a projected normal (PN) model. We illustrate the use of a PN mixed-effects model on three repeated measures data sets with circumplex measurements from inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…To evaluate the contributions of body condition, daylength, latitude, and longitude to the daily timing of activity, we performed circular mixed-effects model analyses using the R package bpnreg ( 55 ). This package implements circular regression and circular mixed-effects regression models as described by Cremers et al ( 28 ), Cremers and Klugkist ( 56 ), Cremers et al ( 57 ), and Cremers et al ( 58 ). First, the circular outcome “Drift” was coded such that 0° represents time of sunrise and 180° represents time of sunset independent of the date.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the contributions of body condition, daylength, latitude, and longitude to the daily timing of activity, we performed circular mixed-effects model analyses using the R package bpnreg ( 55 ). This package implements circular regression and circular mixed-effects regression models as described by Cremers et al ( 28 ), Cremers and Klugkist ( 56 ), Cremers et al ( 57 ), and Cremers et al ( 58 ). First, the circular outcome “Drift” was coded such that 0° represents time of sunrise and 180° represents time of sunset independent of the date.…”
Section: Methodsmentioning
confidence: 99%
“…Further, comprehending and demonstrating proper interpersonal behaviour has proved its effectiveness in psychology to study interpersonal processes, personality traits, and relationship functioning (Kiesler and Auerbach, 2003;Pincus and Gurtman, 2006;Locke et al, 2017). Studies have suggested that good quality interpersonal relationships and behaviour are important for peoples' social functioning and mental health (Cremers et al, 2021). Lately, the authors in (Firdaus et al, 2022b) have demonstrated that inculcating politeness in the agent based on the user's personal profile, such as gender and age group makes the dialogue agent capable of identifying subtle language changes while conversing with different users.…”
Section: Related Workmentioning
confidence: 99%
“…polite, moderately_polite and impolite, respectively. The different interpersonal behaviour labels following the two-dimensional IPC model (Cremers et al, 2021) that we use in our work are: directing (Dg), helpful (Hl), understanding (Ug), complaint (Ct), imposing (Ig), confrontational (Cl), dissatisfied (Dd) and uncertain (Un). This interpersonal behaviour annotation list has been extended to incorporate one more label, namely empathetic (Em), considering the significance of empathy in therapy (Sharma et al, 2020(Sharma et al, , 2021Saha et al, 2022).…”
Section: Sentiment Politeness and Interpersonal Behaviour Annotationmentioning
confidence: 99%